A BIG DATA DASHBOARD ARCHITECTURE FOR A COMPUTABLE INTELLIGENT CITY - Kourtit, Karima; Nijkamp, Peter (BDC. Bollettino Del Centro Calza Bini, 2017)
This paper aims to sketch the principles and design of advanced smart city research from the perspective of digital big data, against the background of the emerging “New Urban World”. This study takes its starting point in the need for up-to-date and knowledge-based decision support systems for modern cities and sketches the cornerstones of an “Urban Dashboard” for modern urban policy analysis. Keywords: trading zone, integrated conservation, sustainable development